Preliminary Part - Gaurishankar Campus, (GS WOW: Wisdom of Worthy Research Journal, 2025)
GS WOW: Wisdom of Worthy Research Journal is a Refereed Interdisciplinary Academic Research Journal of Gaurishankar Campus located at Nijgadh, Bara, Nepal. In the ever-evolving landscape of academia, Gaurishankar Campus, Nijgadh, proudly presents its scholarly endeavor, the “Wisdom of Worthy Research Journal” (GS WOW). This distinguished journal serves as a beacon of intellectual exploration, fostering a culture of rigorous academic inquiry and interdisciplinary collaboration. Through its pages, GS WOW seeks to disseminate cutting-edge research, insights, and perspectives, thereby contributing to the global academic discourse.With a commitment to nurturing intellectual curiosity and academic excellence, the campus has become a hub for scholars, researchers, and students dedicated to pushing the boundaries of knowledge. The GS WOW is dedicated effort of the campus to unveil the Pinnacle of Academic Excellence with the Wisdom of Worthy Research publication globally to promote Campus stands as a bastion of education and research.Every manuscript submitted to GS WOW undergoes a meticulous peer-review process, ensuring the highest standards of academic rigor and integrity. It values the intersection of diverse academic disciplines, encouraging submissions that bridge gaps and forge connections between different areas of study. Published from Gaurishankar Campus, Nijgadh, the journal has a global perspective, inviting contributions from scholars worldwide. This global outlook enriches the intellectual diversity within the journal.